Acute and chronic arterial and venous effects of captopril in congestive cardiac failure. Issue 6705 (14th October 1989) - Capewell, S.; Taverner, D.; Hannan, W. J.; Muir, A. L.
Abstract : OBJECTIVE--To determine whether captopril alters peripheral venous tone in patients with congestive cardiac failure. DESIGN--Open study of patients at start of captopril treatment and three months later. SETTING--A hospital gamma camera laboratory. PATIENTS--16 Men with congestive cardiac failure in New York Heart Association class II or III, aged 57-73. INTERVENTIONS--Patients were initially given 500 micrograms sublingual glyceryl trinitrate followed by 25 mg oral captopril. The study was then repeated after three months' captopril treatment. MAIN OUTCOME MEASURES--Previously validated non-invasive radionuclide techniques were used to measure changes in central haemodynamic variables and peripheral venous volumes in the calf. RESULTS--After 25 mg captopril there were falls in blood pressure and relative systemic vascular resistance and increases in cardiac index and left ventricular ejection fraction. This was accompanied by a 16% increase in peripheral venous volume (95% confidence interval 13.4% to 18.4%, p less than 0.01), which compared with an 11% increase after 500 micrograms glyceryl trinitrate (10% to 12%, p less than 0.01). Eleven patients were restudied after three months' continuous treatment with captopril. The resting venous volume was higher than it had been initially, by about 10%, and increased by a further 8.4% after 25 mg captopril (5.4% to 11.4%, p less than 0.05). CONCLUSIONS--Captopril is an important venodilator. Venous and arterial dilatation are produced short term and during long term treatment.